BRIEF INFORMATION ABOUT CONTACTS BETWEEN MUSLIMS OF DAGESTAN AND THE VOLGA-URAL REGION IN THE XVIII-XX CENTURIES. - Sihaliev, Samil' Sihalievic (History, Archeology and Ethnography of the Caucasus, 2020)
Religious contacts of Muslims of Dagestan and the Volga-Ural region have not been in the focus of any particular research till date. Scarce information from various Tatar theologians, who studied in Dagestan at the end of the 17th – 18th centuries, have already been mentioned by Tatar researchers. However, numerous Arabographic sources in Arabic and Tatar show close contacts of the Muslim elite of these two regions, starting from the Middle Ages. The present article aims to review available sources about the educational and scientific contacts of Dagestanis, Tatars, and Bashkirs. The sources available and analyzed in the article revealed the bilateral nature of these contacts. While at the end of the 17th – 18th centuries a number of Tatar theologians received a proper education in Dagestan and opened madrasahs in the Volga-Ural region according to the Dagestan type, then starting from the second half of the 19th century one can observe a quiet strong influence of ideas that were widespread in the Volga-Ural region on the Dagestan intellectual elite. Moreover, starting from the 20th century, Tatar journals, textbooks and scientific literature began to penetrate widely into Dagestan, as evidenced by their considerable number of manuscripts and old printed books in private collections. Mutual contacts of Muslims of Dagestan and the Volga-Ural region were due to various reasons – traveling in order to receive education, exile, commercial affairs, personal correspondence, etc. The mixing and interpenetration of the educational, scientific traditions of the Muslims of these two regions led to their wider cultural development and closer integration into various institutions of the Russian Empire.
Keywords: Dagestan; Volga-Ural region; religious contacts; Islamic education; Nazir ad-Durgili; Riza Fahretdin; al-Kuduki; Abusufyan Akaev.